Creation - McLure, Kirstie; Couper, Heather; Everest, Mark ([S.l.] : TLC Video [production company] ; [S.l.] : Discovery Channel Video, 1999)
Scientists and insightful researchers from around the world explain theories and discoveries about Big Bang and our expanding Universe's future
Writer, Mark Everest, Nigel Henbest ; editor, Raimondo Aiello ; executive producer, Stuart Carter
Narrator: John Hurt
Keywords: Cosmology; Astronomy